2022
DOI: 10.3233/jad-215024
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Distribution of 18F-THK5351 Positron Emission Tomography in Alzheimer’s Disease Continuum

Abstract: Background: Alzheimer’s disease (AD) is conceptualized as a biological continuum encompassing the preclinical (clinically asymptomatic but with evidence of AD pathology) and clinical (symptomatic) phases. Objective: Using 18F-THK5351 as a tracer that binds to both tau and MAO-B, we investigated the changes in 18F-THK5351 accumulation patterns in AD continuum individuals with positive amyloid PET consisting of cognitively normal individuals (CNp), amnestic mild cognitive impairment (aMCI), and AD and cognitivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…In another study, individuals classified as Aβ-negative CU, Aβ-positive CU, Aβ-positive MCI, and Aβ-positive AD showed a trend toward longitudinal tau accumulation predominantly in Braak I–II, I–III, IV–V, and V–VI ROIs, respectively ( 25 ). In Nihashi et al., 18 F-THK5351 binding in Braak ROIs did not differ between Aβ-positive and Aβ-negative CU individuals ( 23 ). MCI and AD individuals had higher binding than CU participants in Braak I–IV ROIs and in all Braak ROIs, respectively ( 23 ).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…In another study, individuals classified as Aβ-negative CU, Aβ-positive CU, Aβ-positive MCI, and Aβ-positive AD showed a trend toward longitudinal tau accumulation predominantly in Braak I–II, I–III, IV–V, and V–VI ROIs, respectively ( 25 ). In Nihashi et al., 18 F-THK5351 binding in Braak ROIs did not differ between Aβ-positive and Aβ-negative CU individuals ( 23 ). MCI and AD individuals had higher binding than CU participants in Braak I–IV ROIs and in all Braak ROIs, respectively ( 23 ).…”
Section: Resultsmentioning
confidence: 88%
“…For stage VI, the topographic definition was relatively similar among studies, with the presence of the paracentral, postcentral, and precentral gyri highlighted in most descriptions ( 11 , 17 , 18 , 20 , 22 , 28 ). Divergence was found in the allocation of the cuneus: studies using second-generation ligands associated this structure with stage V ( 17 , 22 , 25 , 26 ), and those using first-generation ligands associated it with stage VI ( 11 , 18 , 20 , 21 , 23 , 28 ).…”
Section: Resultsmentioning
confidence: 99%
“…THK5117 and THK523 were primary ligands of the THK group and for healthy control (HC) they exhibited large amount of white matter retention; it was continuously enhanced over the group and the final compound [ 18 F]THK5351 showed much improved results as compared with starting compounds. Maximum uptake in HC was observed for [ 18 F]AV‐1451 (Leuzy et al, 2022; Nihashi et al, 2022; Pascoal et al, 2020; S. Roy et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Autoradiographic data from [ 18 F]THK5105 indicated selective recognition of NFTs and neuropil threads in the hippocampus of AD patients (Lemoine et al, 2017). Nonetheless, off-target binding of [ 18 F]THK5351 to monoamine oxidase B (MAO-B) in the basal ganglia and cortex remains a major drawback when interpreting PET images (Harada et al, 2016;Ng et al, 2017;Nihashi et al, 2021). First-generation tau tracers [ 18 F]THK5351, [ 11 C]PBB3 and [ 18 F] flortaucipir all bind to the 3R + 4R combination of tau as in AD (Table 1; Chien et al, 2013;Maruyama et al, 2013;Okamura et al, 2013;Xia et al, 2013;Harada et al, 2016;Betthauser et al, 2017;Ono et al, 2017).…”
Section: First-generation Tau Tracersmentioning
confidence: 99%
“…Chiotis et al showed that [ 18 F]THK5317 accurately predicts the degree of cognitive decline in patients with AD (Chiotis et al, 2020). Nihashi et al (2021) suggested that the quantity of [ 18 F]THK5351 uptake in the brain of AD patients inversely correlated with hippocampal volume and neuropsychological assessment, implying that [ 18 F]THK5351 may be a candidate for monitoring AD disease progression. Ezura et al (2021) compared differential binding of [ 18 F]THK5351 to different tauopathies and found that high [ 18 F]THK5351 uptake was detected in the precentral and postcentral gyri of CBD patients, in the midbrain of PSP patients and in the parahippocampal gyri of AD patients compared to healthy controls, clearly distinguishing different tauopathies.…”
Section: In Vivomentioning
confidence: 99%